Intelligent computing, communication and devices : proceedings of ICCD 2014, Volume 2 - Jain, Lakhmi C.; Patnaik, Srikanta; Ichalkaranje, Nikhil (Advances in Intelligent Systems and Computing,, 2015)
In the history of mankind, three revolutions which impact the human life are the tool-making revolution, agricultural revolution and industrial revolution. They have transformed not only the economy and civilization but the overall development of the society. Probably, intelligence revolution is the next revolution, which the society will perceive in the next 10 years. ICCD-2014 covers all dimensions of intelligent sciences, i.e. Intelligent Computing, Intelligent Communication and Intelligent Devices. This volume covers contributions from Intelligent Communication which are from the areas such as Communications and Wireless Ad Hoc & Sensor Networks, Speech & Natural Language Processing, including Signal, Image and Video Processing and Mobile broadband and Optical networks, which are the key to the ground-breaking inventions to intelligent communication technologies. Secondly, Intelligent Device is any type of equipment, instrument, or machine that has its own computing capability. Contributions from the areas such as Embedded Systems, RFID, RF MEMS, VLSI Design & Electronic Devices, Analog and Mixed-Signal IC Design and Testing, MEMS and Microsystems, CMOS MEMS, Solar Cells and Photonics, Nano Devices, Single Electron & Spintronics Devices, Space Electronics, and Intelligent Robotics are covered in this volume.